Humility and Arrogance: Their Respective Legal and Ethical Positions in Islam. - RASHID, DR. BURHAN (The journal of contemporary issues in business and government, 2021)
The aim of this paper is to examine various aspects of human behavior and its impact on personal and social life, with a focus on humility and arrogance. Attempt is also made to know the ways and means that can aid in the eradication of moral vices and the cultivation of moral virtues among individuals and societies. Pondering over the original texts, as well as their explanations provided by the scholars, the author has tried best to obtain a deeper understanding of the nature and essence of arrogance and humility, as well as their respective implications. The information gathered is organized systematically in accordance with academic norms. The texts as well as the human experience testify that arrogance is an abominable moral vice that breeds a slew of other moral vices, while humility is the most admirable moral virtue that fosters love and affection among individuals, resulting in mental peace and social solidarity. The paper would make a significant contribution in that it explains almost all the root causes of arrogance and then offers a list of seventeen remedies for removing it from one’s own self (nafs). On the other hand, readers will find a summary of the virtues and advantages of humility in both personal and social life. Furthermore, the remedies discussed for the eradication of arrogance will help us to cleanse ourselves of this spiritual affliction. The tips and methods for acquiring humility that have been discussed will allow us to adorn ourselves with good moral qualities.